RANCANG BANGUN APLIKASI QUICK COUNT PILKADA BERBASIS SMS GATEWAY DENGAN METODE SIMPLE RANDOM SAMPLING (STUDI KASUS KOTA LUBUKLINGGAU) - Arie Yandi Saputra; Deni Apriadi (UNIVERSITAS PELITA HARAPAN, 2018)
Quick Count is a process of gathering information by hundreds or even thousands of volunteers through direct monitoring during voting and vote counting in all or several polling stations (TPS) that exist. Quick Count is not the same as public opinion research or exit polling. Quick Count is not an opinion and does not ask voters who and how they vote, but based on facts because its data is taken directly from TPS based on C1 form that can be accounted for. In the implementation of elections or elections, of course, the interested parties, especially the candidate pair or successful team is in need of information on election results after the election activities closed. This information is needed as a basis for predicting the results of vote counting, identifying fraud and recording inconsistencies between the results obtained and the official results by the election organizers. Of course the benefits of quick count has a strong relationship with the implementation of elections or elections are honest, transparent, fair, and secret. In the execution of quick count activities, many methods can be used and all the methods used must utilize the sampling (sampling frame) based on the existing polution as the data source. The sample can be a list of kelurahan or TPS list in all areas that become the object of research, one of them is Sample Random Sampling technique. Keywords: Quick Count, Simple Random Sampling, sms gateway